Evidence of a Causal Relationship between Serum Thyroid-Stimulating Hormone and Osteoporotic Bone Fractures. Issue 6 (19th November 2021) - Soto-Pedre, Enrique; Siddiqui, Moneeza K.; Mordi, Ify; Maroteau, Cyrielle; Soto-Hernaez, Jimena; Palmer, Colin N.A.; Pearson, Ewan R.; Leese, Graham P.
Abstract : Objective: We aimed to validate the association of genome-wide association study (GWAS)-identified loci and polygenic risk score with serum thyroid-stimulating hormone (TSH) concentrations and the diagnosis of hypothyroidism. Then, the causal relationship between serum TSH and osteoporotic bone fracture risk was tested. Methods: A cross-sectional study was done among patients of European Caucasian ethnicity recruited in Tayside (Scotland, UK). Electronic medical records (EMRs) were used to identify patients and average serum TSH concentration and linked to genetic biobank data. Genetic associations were performed by linear and logistic regression models. One-sample Mendelian randomization (MR) was used to test causality of serum TSH on bone fracture risk. Results: Replication in 9, 452 euthyroid individuals confirmed known loci previously reported. The 58 polymorphisms accounted for 11.08% of the TSH variation ( p < 1e−04). TSH-GRS was directly associated with the risk of hypothyroidism with an odds ratio (OR) of 1.98 for the highest quartile compared to the first quartile ( p = 2.2e−12). MR analysis of 5, 599 individuals showed that compared with those in the lowest tertile of the TSH-GRS, men in the highest tertile had a decreased risk of osteoporotic bone fracture (OR = 0.59, p = 2.4e−03), while no difference in a similar comparison was observed in women (OR = 0.93, p = 0.61). Sensitivity analysis yielded similar results. Conclusions: EMRs linked to genomic data in large populations allow replication of GWAS discoveries without additional genotyping costs. This study suggests that genetically raised serum TSH concentrations are causally associated with decreased bone fracture risk in men.